El respeto a la interculturalidad y su influencia en el comportamiento social de los estudiantes de décimo año de educación general básica - Parco Masasela, María Flor (2018)
In the present study, it was developed under the general objective of: Respect for interculturality and its influence on the social behavior of the tenth year students of general basic education of the Intercultural Bilingual Fiscal Education Unit "Fernando Daquilema", as well as the teachers, students and parents. In order to determine if the level of respect for diversity that is developed in the classroom by the guidance of teachers and parents, positively influences the regulation of student behavior………